Temozolomide Treatment for Pediatric Refractory Anaplastic Ependymoma with Low MGMT Protein Expression. Issue 1 (25th August 2015) - Komori, Kazutoshi; Yanagisawa, Ryu; Miyairi, Yosuke; Sakashita, Kazuo; Shiohara, Masaaki; Fujihara, Ikuko; Morita, Daisuke; Nakamura, Tomohiko; Ogiso, Yoshifumi; Sano, Kenji; Shirahata, Mitsuaki; Fukuoka, Kohei; et al.
Abstract : The benefit of postoperative chemotherapy for anaplastic ependymoma remains unknown. We report two pediatric patients with refractory anaplastic ependymoma treated with temozolomide (TMZ). We did not detect O 6 ‐methylguanine‐DNA methyltransferase (MGMT) promoter methylation in tumor samples; however, MGMT protein expression was low. With TMZ treatment, one patient had a 7‐month complete remission; the other, stable disease for 15 months. Three other patients did not respond to TMZ; two had high and one low MGMT expression, and two showed no MGMT promoter methylation. These findings suggest that TMZ may be effective for pediatric refractory anaplastic ependymoma with low MGMT protein expression. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.